(3GdCOGA GdeGdj h CKQg Ydi YhGFO CSge GdTQcGJs - (3eMeO eMehO(B, (3GdNWjHs ((3YeGf(B:s (3OGQ GdMGeO(B,s, 2010)
(3eaghe GdGOGA GdeGdj h ebGjjSg , ebGjjS GdGOGA GdeGdj h CKQgG Ydi YhGFO GdCSge , ebGjjS h eMOOGJ YhGFO GdCSge , GdYhGed GdGbJUGOjI GdeDKQI Ydi YhGFO GdCSge , hGbY GdTQcGJ GdUfGYjI aj HhQUI YeGf (B: (3fTGI bWGY GdUfGYI , JWhQ GdTQcGJ GdUfGYjI GdeOQLI aj HhQUI YeGf , GdGWGQ GdJMdjdj ddOQGSI (B.s
(3eQGLY U(B.179 (3; edGMb U(B.153 (3;LOGhd U(B.13 (3; GTcGd U(B.14s
Keywords: (3GdCSges; (3GdTQcGJs; (3eMGSHI GdTQcGJs